Interactive Panel: a strategy to reveal views on interprofessionality (Research, Society and Development, 2020)
Interprofessionality has been presented as a strategy to reorient health education and work, in order to respond to the demands of the complexity of health-disease processes. The concepts that underlie this strategy are present in the health field, however, there is a lack of discussion on teamwork and interprofessionality in the social, human or technological areas, demonstrating limitations in practices of these disciplines based on the concepts. This report aims to describe an experience developed by PET-Health/Interprofessionality in a college education institution in Ceará, in which we sought to discuss, through an active learning methodology, interprofessionality in areas that are dialogic to health. During the exercise, it was observed the use of concepts about team work, such as multiprofessionality and interprofessionality as synonyms, showing an insufficient theoretical basis on these concepts. This conceptual distinction is reflected in the inadequate characterization of practices. Furthermore, the interest of the participants in the recognition and appropriation of concepts is examined. The experience proved to be relevant because it enabled reflections on Interprofessionality in areas that scarcely explore it and announces the need to expand the discussion of interprofessionality beyond the area of ​​health experience, since the production of health and life goes beyond disciplinary and professional boundaries of health.